Miskonsepsi dalam Pembelajaran Matematika: Tinjauan Literatur Pada Materi Eksponen - Nurzaenah; Peni, Nur Robiah Nofikusumawati (Papanda, 2025)
In junior high school mathematics, exponents are a fundamental topic that underpins the understanding of more advanced concepts such as logarithms and exponential equations. However, many students still struggle to fully grasp this concept, leading to various forms of misconceptions. Using a systematic literature review approach, this study aims to examine the types of misconceptions, their causes, and the implications for teaching and learning. The literature search was conducted through Google Scholar and Dimension AI databases using specific keywords and inclusion criteria, namely: articles discussing the analysis of misconceptions in teaching exponents at the junior high school level, published between 2020 and 2025, and sourced from indexed national and international journals. The selection process yielded four articles that met the criteria and were relevant for further analysis. The review findings indicate that the types of misconceptions found among students include generalization, notation, overspecialization, and mathematical language. The causes of these misconceptions are classified into internal factors (such as incorrect preconceptions and a tendency to memorize without understanding), external factors (such as non-contextual teaching approaches and lack of visual media), and differences in students' academic abilities. These findings imply the need for diagnostic assessment, meaningful learning, the use of concrete media, and differentiated instruction strategies tailored to students' needs to minimize misconceptions and enhance conceptual understanding of exponents.